IMAGE BUILDING THROUGH EFL TEXTBOOK ‘MY PALS ARE HERE’ TO STUDENTS IN KUPANG, EASTERN INDONESIA - Peggy Jonathans (Indonesian EFL Journal, 2018)
English textbook is supposed to display society traditions and civility to encourage intellectual conversation among students. Even at earliest stage, young students can grow thoughtful principles of living in diversity and respectful among multicultural and religious community. The heart of moral values in students’ English book is expected to effectively address social and moral problems of society and to maintain the harmony of living. ‘My Pals are Here’ English textbooks for primary schools, presents EFL/ESL Asia themes. This motivates one private primary school in Kupang, eastern Indonesia to use this book believing that their students are part of international and wider community and engaging them in more Asia perspectives with attractive and colorful world teaching them many good values. By elaborating humanistic approach in the book content, this book achieves to deliver daily issues encountered by Asian children living more progressively with the introduction of many discourses in Asia and beyond without such pigeon holed the context of the book to very narrow scope. This discussion paper therefore aims to look at and discuss the input established within the book through the language and topic contents, as well as social and cultural values underlying the content, and the virtues addressed to the children. Images built within this book depicted through illustrations, figures, negotiation of meanings and interaction which extensively encouraged and performed from tasks given. The textbook succeeds to show self-identity of Asia throughout the content. Keywords: Language Content; Subject Content; Moral Values; Images.